2021
DOI: 10.1093/ofid/ofab476
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-effectiveness of Cefazolin Compared With Antistaphylococcal Penicillins for the Treatment of Methicillin-SensitiveStaphylococcus aureusBacteremia

Abstract: Background Methicillin-sensitive Staphylococcus aureus (MSSA) bacteremia is associated with significant morbidity, mortality, and hospitalization costs. Cefazolin and anti-staphylococcal penicillins (ASPs), such as nafcillin, are the preferred treatments for MSSA bacteremia. The aim of this study was to compare the cost-effectiveness of each approach. Methods We constructed a decision-analytic model comparing the use of cefaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The case for cefazolin in MS-SAB has been incrementing evidence. In a cost effectiveness analysis Pliakos et al concluded to a cost saving of $97 157 per death averted with cefazolin compared to antistaphylococcal penicillins for MS-SAB [25 ▪ ]. In a post-hoc analysis of a multicentre cohort of methicillin-susceptible Staphylococcus aureus (MSSA) infectious endocarditis, Lecomte et al found similar mortality (24% vs. 29%) but less frequent treatment discontinuation for adverse events – most commonly AKI - with cefazolin than antistaphylococcal penicillins (0% vs. 8%).…”
Section: Antibiotic Choicementioning
confidence: 99%
“…The case for cefazolin in MS-SAB has been incrementing evidence. In a cost effectiveness analysis Pliakos et al concluded to a cost saving of $97 157 per death averted with cefazolin compared to antistaphylococcal penicillins for MS-SAB [25 ▪ ]. In a post-hoc analysis of a multicentre cohort of methicillin-susceptible Staphylococcus aureus (MSSA) infectious endocarditis, Lecomte et al found similar mortality (24% vs. 29%) but less frequent treatment discontinuation for adverse events – most commonly AKI - with cefazolin than antistaphylococcal penicillins (0% vs. 8%).…”
Section: Antibiotic Choicementioning
confidence: 99%
“…Similar economic evaluation research tended to ignore the proportion of patients with CAP who are misdiagnosed with PTB [18,21,23,30,33,34]; therefore, to explore the reliability of the conclusions, and to further verify the value of the differential diagnosis of PTB, a scenario analysis in which PTB was not considered was performed.…”
Section: Scenario Analysismentioning
confidence: 99%
“…First, the study found that the use of fluoroquinolone antibiotics in the diagnosis and treatment of CAP patients with unclear symptoms increases the risk of delaying the diagnosis of tuberculosis [12]. Second, in the previous articles studying the economics of CAP drugs, the misdiagnosis of tuberculosis patients had not been considered [18,21,23,31,33,34]. This study considered that a certain proportion of patients with CAP were misdiagnosed with tuberculosis and performed a CUA analysis on this basis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the question if Cefazolin should be used for central nervous system infections, a recent review concludes Cefazolin being a reasonable option for a variety of CNS infections [ 6 ]. Cefazolin has been attributed less side effects than ASP and seems to result in health care cost savings [ 7 ]. Reviews and meta-analyses have suggested that cefazolin is at least as effective as ASP while possibly being safer and associated with less acute kidney injury [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%